Source Rock Potential of Nampol Formation Sumbermanjing Area, Malang, East Java, Indonesia Based on Geochemistry Analysis of the Selected Sample - Carolus Prasetyadi; Achmad Subandrio; M. Gazali Rachman; Antu Ridha Falkhan Barizi; Muhammad Muslim (Scientific Contributions Oil and Gas, 2022)
Nampol Formation of the Southern Mountains of eastern Java (Indonesia) has a distribution from its type location in Pacitan to the South Malang area. In the research area, this formation consists of clastic limestone with black shale inserts, claystone, siltstone, carbonate sandstone and claystone which are interpreted to be deposited in a restricted platform interior environment with closed water circulation. A total of three samples were analyzed to evaluate the organic matter content, kerogen type, thermal maturity, and hydrocarbon generating potential. Samples were taken from clastic carbonate deposits of the Nampol Formation. Based on the results of geochemical analysis, the three samples from the Nampol Formation have a TOC content of 3.48 - 26.18 wt% and possess good to excellent hydrocarbon generating potential. Hydrogen Index (HI) values for the studied samples ranged from 43 to 86 mg HC/g TOC and S1+S2 results ranged from 1.52 to 19.55 mg HC/g rock, indicating that the sample has the potential to produce gas. All three samples were dominated by Type III kerogen and were thus considered gas prone based on the HI vs. Tmax diagrams. The three samples were categorized as thermally immature based on Tmax pyrolysis analysis and Vitrinite Refl ectance (VR) values in the range of 0.44 to 0.46 % Ro. Based on the results obtained, the black shale and coal in the Nampol Formation has the capability to generate hydrocarbon but are considered as an immature source rock that can be predicted to produce gas at its peak maturity.